Electrochemical Determination of Tartrazine Using a Graphene/Poly(L-Phenylalanine) Modified Pencil Graphite Electrode - Tahtaisleyen, Selen; Gorduk, Ozge; Sahin, Yucel (TAYLOR & FRANCIS INC, 2020)
The rapid and accurate determination of tartrazine is necessary for human health and environment. In this study, a sensor platform was developed for the electrochemical determination of tartrazine. For this purpose, graphene and poly(L-phenylalanine) were attached to the pencil graphite electrode surface and the determination process of tartrazine was performed with the developed sensor. The conventional three-electrode system was used throughout all electrochemical measurements. A pencil graphite electrode was used as the working electrode, a Ag/AgCl electrode was employed as the reference electrode, and a platinum wire was used as the counter electrode. Under the optimized conditions, experimental measurements were performed with differential pulse voltammetry and cyclic voltammetry using the oxidation peak current of tartrazine. The limit of detection and limit of quantitation values for tartrazine were determined to be 1.54 mu M and 5.14 mu M, respectively, based on signal-to-noise ratios of 3 and 10. Cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy were used for the characterization of sensor. The applicability of the sensor platform to the real samples was investigated and the recovery values were from 98.71 to 104.44%. The developed device has been found to be applicable to juice sample. The relative standard deviation was calculated and the modified electrode was found to have good repeatability. As a result, the developed sensor for tartrazine was simple, economical, selective, and sensitive.
Keywords: Cyclic voltammetry; differential pulse voltammetry; food additive; graphene; L-phenylalanine; pencil graphite electrode; tartrazine; SUNSET YELLOW; VOLTAMMETRIC DETERMINATION; SENSITIVE DETERMINATION; SYNTHETIC COLORANTS; GRAPHENE OXIDE; SOFT DRINKS; ONE-STEP; FOOD; NANOCOMPOSITE; FABRICATION; Chemistry